Euler-Poincare characteristics of classes of disordered media - Mecke, Klaus; et al. (Physical Review E, 2001)
We consider a family of statistical measures based on the Euler-Poincare characteristic of It-dimensional space that are sensitive to the morphology of disordered structures. These measures embody information from ever?, order of the correlation function but can be calculated simply by summing over local contributions. We compute the evolution of the measures with density for a range of disordered microstructural models; particle-based models, amorphous microstructures, and cellular and foamlike structures. Analytic results for the particle-based models are given and the computational algorithm verified. Computational results for the different microstructures exhibit a range of qualitative behavior. A length scale is derived based on two-point autocorrelation functions to allow qualitative comparison between the different structures. We compute the morphological parameters for the experimental microstructure of a sandstone sample and compare them to three common stochastic model systems for porous media. None of the statistical models are able to accurately reproduce the morphology of the sandstone.